Impact of the armed conflict in Colombia: consequences in the health system, response and challenges - Oscar Bernal; Tatiana Garcia-Betancourt; Sebastián León-Giraldo; Lina Marcela Rodríguez; Catalina González-Uribe (Conflict and Health, 2024)
Abstract Introduction In Colombia, research on health and conflict has focused on mental health, psychosocial care, displacement, morbidity, and mortality. Few scientific studies have assessed health system functioning during armed conflicts. In a new period characterized by the implementation of the peace agreement with the Revolutionary Armed Forces of Colombia (FARC) armed group, understanding the effects of armed conflict on the health system, the functions, and institutions shaped by the conflict is an opportunity to understand the pathways and scope of post-conflict health policy reforms. Therefore, this study was conducted to assess the effects of armed conflict on the health system, response, and mechanisms developed to protect medical missions during armed conflict in Colombia. Methods This research was conducted using a qualitative approach with semi-structured interviews and focus group discussions. The qualitative guide collected information in four sections: (1) conflict and health system, effects and barriers in health service provision, (2) actions and coordination to cope with those barriers, (3) health policies and armed conflict, and (4) post-accord and current situation. Twenty-two people participated in the interviews, including eight policymakers at the national level and seven at the local level, including two NGOs and five members of international organizations. An academic project event in December 2019 and four focus groups were developed (World Cafe technique) to discuss with national and local stakeholders the effects of armed conflict on the health system and an analytical framework to analyze its consequences. Results The conflict affected the health-seeking behavior of the population, limited access to healthcare provision, and affected health professionals, and was associated with inadequate medical supplies in conflict areas. The health system implemented mechanisms to protect the medical mission, regulate healthcare provision in conflict areas, and commit to healthcare provision (mental and physical health services) for the population displaced by conflict. Conclusion The state’s presence, trust, and legitimacy have significantly reduced in recent years. However, it is crucial to restore them by ensuring that state and health services are physically present in all territories, including remote and rural areas.